2015
DOI: 10.1177/0192623315587921
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Gland Background Findings in CD-1 (Crl:CD-1(ICR)BR) Mice from 104-week Carcinogenicity Studies

Abstract: The authors performed a retrospective study to determine the incidences of spontaneous findings in the adrenal glands of control CD-1 mice. Data were collected from 2,163 mice from control dose groups in 104-week carcinogenicity studies carried out between 2000 and 2010. Adrenal gland nonproliferative lesions were more common in males than in females. In males, the most common nonproliferative lesions were cortical hypertrophy, cortical atrophy, pigment deposition/pigmentation, cysts, and extramedullary hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Up to 70% of the irradiated animals presented the change, whereas the background incidence is usually below 10%. 38 This needs to be considered when evaluating the toxicity of the GTMP.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 70% of the irradiated animals presented the change, whereas the background incidence is usually below 10%. 38 This needs to be considered when evaluating the toxicity of the GTMP.…”
Section: Discussionmentioning
confidence: 99%
“…They can also contribute, albeit at low frequency, to adrenal cortex replenishment in the adult (6,9,18,19,33), and can be mobilized upon gonadectomy, giving rise to adrenal neoplasia (34,35), presenting characteristics of adrenogonadal cells such as GATA4, LHR, and PDGFRα expression (19). Interestingly, aging mouse adrenals also present subcapsular accumulation of spindle-shaped cells (36,37). Although lineage tracing has shown that gonadectomy-induced lesions arise in part from WT1/GLI1-positive cells, the origin of spindle-shaped cells in the aging adrenal cortex is not as clear, even though GLI1-positive cells may contribute to their appearance (19).…”
Section: Discussionmentioning
confidence: 99%
“…Aging female mice of A, C57BL/6, BALB/c DBA/2, 6 CD-1 (Crl:CD 1(ICR)BR), 49 and FVB 36 strains have a higher incidence of adrenal subcapsular fusiform cell hyperplasia compared to males, although these changes were minimally present in female NSG mice.…”
Section: Discussionmentioning
confidence: 99%